Experimental and numerical analysis of heat transfer in polymer composites with metallic inclusions using virtual element method - Sina Tahouni; Mohammad Azhdari; Ghader Rezazadeh; Mohammad Fathalilou; Raghav Pathak; Tim Ricken; Seyed Morteza Seyedpour (Materials & Design)
Polymer composites are extensively employed in aerospace, automotive, electronics, and biotechnology as a result of their tunable properties and high strength-to-weight ratios. Development of trustworthy and effective components depends on an awareness of their thermal behavior. Heat flow in polymer composites with different iron particle concentrations is investigated in this work using the Virtual Element Method (VEM). Simulations were carried out utilizing the Maxwell and Bruggeman models in addition to a new virtual element property (VEP) technique which independently assigns thermal properties to mesh elements. Designed and tested under laser irradiation, experimental samples comprising 10 % to 50 % iron by volume were produced. High-accuracy sensors captured temperature responses; they were then matched with simulation findings. Outperformance of the effective conductivity models, the VEP approach displayed great correlation with experimental data for both radial and deep temperature measurements. The results show how faithfully VEM can replicate heat transfer in heterogeneous composites with intricate geometries. VEM results showed strong agreement with experimental data and the mean absolute errors were mostly below 5 % and 10 %, and only increased to 15 % in the case of 40 % iron content. In the 50 % iron sample, the error rose to 20 %, likely due to the formation of idealized thermal chains in the numerical mesh, which may not fully develop in the actual material.